Age-related hearing loss associated with cognitive impairment in the Polish cohort of the PURE study - Połtyn-Zaradna, Katarzyna; Pazdro-Zastawny, Katarzyna; Szcześniak, Dorota; Basiak-Rasała, Alicja; Wołyniec, Maria; Zatońska, Katarzyna; Zatoński, Tomasz (Frontiers in Aging Neuroscience, 2025)
BackgroundCurrently, dementia is estimated to be the seventh most common cause of death and one of the leading causes of disability and dependency among older people worldwide. The main aim of this study is to analyze the association of presbycusis and cognitive impairment in the study population. Secondary aim is to identify the risk and prevalence of presbycusis taking into account bio- socio-demographic factors among the residents of Wrocław and surrounding villages.MethodsData from 891 participants (559 women and 332 men; mean age: 60.7 years; range: 39–81) in the Polish cohort of the PURE study who met the inclusion criteria for the PURE MIND sub-study and who had a cognitive and functional assessment completed (MoCA test, DSST test, TMT parts A and B, CES-D, SAGE test).ResultsHearing loss was a significant risk factor for cognitive impairment as assessed using the MoCA, DSST, TMT A and TMT B tests. Mild cognitive impairment (MoCA < 26 score) was present in nearly half of those with hearing loss compared to 26.0 per cent of those without hearing loss (p = 0.036). Hearing loss increased the chance of MCI almost 1.5-fold [OR 1.34; CI 0.93–1.93]. Multivariate regression analysis showed that those with hearing loss, hypertension and diabetes scored significantly lower (worse) on the MoCA test (by −0.52 points [95% CI −0.99 to −0.06]; −0.48 points [95% CI −0.96 to −0.01] and −0.69 points [95% CI −1.16 to 0.23], respectively). Excessive body weight and diabetes increased the chance of developing hearing loss by more than 1.5-fold [OR 1.64; CI 1.03–2.68; OR 1.59; CI 1.04–2.41, respectively]. Hearing loss was significantly more common among men (22.3%), irrespective of level of education. The MCI was more common among rural residents (54.8% vs. 34.8%) and in participants with lower levels of education.ConclusionAge-related hearing loss is a modifiable risk factor for dementia, emphasizing the importance of routine hearing assessments and timely interventions. Integrating hearing loss management with strategies targeting vascular and metabolic health can help mitigate cognitive decline.